Correcting misinformation using theory-driven messages: HPV vaccine misperceptions, information seeking, and the moderating role of reflection - Borah, Porismita; Kim, Sojung; Xiao, Xizhu; Lee, Danielle Ka Lai (Atlantic journal of communication, 2022)
Despite the fact that scientific evidence has repeatedly affirmed the safety of the Human Papillomavirus (HPV) vaccine, unconfirmed stories on social media that allege the vaccine is harmful has led to vaccination refusal, which drastically hampers immunization rates. Although social media makes it easy for the spread of misinformation, these platforms are also suitable for misinformation correction. The current study employs an experimental design to 1) test theory-based correction messages using loss- vs. gain-frames, to combat misinformation online in the context of Facebook, 2) extend the effects of correction messages from misperceptions to behavioral intentions, and 3) examine the conditional effects of reflection which is one of the most important variables for information processing. Our findings demonstrated that individuals with low reflection had lower misperceptions about the vaccine when exposed to loss-framed messages. However, exposure to loss- or gain-framed messages did not seem to differ the misperceptions for individuals with high reflection. Additionally, our findings showed that loss-framing elicited lower information seeking intention among individuals with low reflection. Implications are discussed.